Pharmacological activity of Salvia lavandulifolia and chemical components of its essential oil. A Review - Porres-Martínez, María; Carretero Accame, Mª Emilia; Gómez-Serranillos Cuadrado, Mª Pilar (Lazaroa, 2013)
Salvia lavandulifolia Vahl. is a plant of Iberian Peninsula origin that belongs to the genus Salvia. Phytochemical evaluation of the plant indicated the presence of flavonoids, triterpenoids, diterpenoids and monoterpenes. Its essential oil is rich in various bioactive compounds (like 1,8-cineole or α-pinene). The plant has been traditionally used for its spasmolytic, antiseptic, analgesic, sedative and anesthesic activities. Pharmacological studies of the plant have demonstrated its reputation as aromatic plant to enhance memory and anti-dementia drug by the inhibition of cholinesterase enzyme. The species also possesses a wide range of pharmacological uses including: antioxidant, anti-inflammatory, estrogenic and central nervous system depressant properties, relevant to the treatment of Alzheimer´s disease. The present review summarizes the information concerning the botany, ethnopharmacology, phytochemistry, pharmacological activities and toxicity of the Salvia lavandulifolia plant, because these findings suggest the need for further research of this plant.